(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Excessive screen time and reduced physical activity are emerging risk factors for childhood visual impairments. This study explores the association between screen exposure, physical activity levels, and visual health among school-aged children. The findings indicate that children with visual impairments spend an average of 4.2 hours per day on screens, significantly more than their peers with normal vision (2.9 hours, p < 0.001). Additionally, children with vision problems engage in less physical activity (43.1 minutes per day) compared to those with normal vision (60.7 minutes, p < 0.001). These results highlight the urgent need for balanced screen use and increased outdoor activity to mitigate vision deterioration.